Pengenalan Konsep Matematika dalam Permainan Monopoli Kelas B di TK Putri Ramadhani Kota Parepare - Nurhamna; Nurhaskin; Ashari, Novita; Jalil, Nurlina; Arina Mustaka, Nurul; Fahrani Dasman, Elsa (PG PAUD Universitas Negeri Surabaya, 2023)
The introduction of mathematical concepts in learning is not well understood by children because of the limited types of media used. The purpose of this study was to determine the level of understanding in children regarding the mathematical concept in the introduction of geometric shapes using monopoly media. The method used in this research is the descriptive qualitative method, in which researchers go directly to the field to collect data needed in research such as observation, interviews, and documentation. The subjects used in this study were group B children at Putri Ramadhani Kindergarten, totaling 20 people, 10 boys, and 10 girls. The results of this research are that children cancan recognize geometric shapes, count from numbers 1-20, match number symbols with numbers, and children are also able to talk in front of their friends about what children get while playing monopoly games.